Effect of Glepaglutide, a Long‐Acting Glucagon‐Like Peptide‐2 Analog, on Gastrointestinal Transit Time and Motility in Patients With Short Bowel Syndrome: Findings From a Randomized Trial. Issue 8 (5th February 2020) - Hvistendahl, Mark Krogh; Naimi, Rahim Mohammad; Enevoldsen, Lotte Hahn; Madsen, Jan Lysgaard; Fuglsang, Stefan; Jeppesen, Palle Bekker
Abstract: Background: Patients with short bowel syndrome (SBS) and distal‐bowel resections lack neuroendocrine feedback regulations, potentially resulting in rapid gastrointestinal (GI) transit. The objective was to assess the efficacy of glepaglutide, a long‐acting glucagon‐like peptide‐2 analog, on GI transit in patients with SBS. Methods: In this single‐center, double‐blind, dose‐finding, phase 2 trial, patients with SBS were randomly assigned to 3 treatments (0.1, 1, and 10 mg) in a 2‐period crossover design. Each treatment period included 3 weeks of daily, subcutaneous glepaglutide injections separated by a washout period of 4–8 weeks. Endpoints were changes from baseline and included scintigraphy, wireless motility capsule (WMC, SmartPill Given Imaging, Ltd, Yokneam, Israel), and paracetamol absorption test. Results: A total of 18 patients were randomized. In the 10‐mg dose group (n = 9), glepaglutide significantly increased time to 10% gastric emptying (GE) of solids by 27 (4–50) minutes (adjusted mean [95% CI]), time to 50%GE of fluids by 40 (1–80) minutes, and time to 10% small bowel–emptying of solids by 21 (1–41) minutes. The WMC transit did not significantly change in any of the dose groups. The maximum paracetamol concentration significantly increased in the 10‐mg dose group; however, the area under the curve remained the same. Conclusion: The prolonged GI transit after glepaglutide treatment, along with demonstrated positive effects on intestinal mucosal growth and potential effects on GI hypersecretions, is believed to contribute to the observed beneficial effects on fecal output (primary endpoint) and associated improvement in intestinal absorption.